Volume and Structure of the Population’s Need for High-Tech Ophthalmological Care in Azerbaijan - B. Kh. Gadzhieva (Oftalʹmologiâ, 2024)
Purpose. Determine the volume and structure of hightech ophthalmological care in Azerbaijan.Materials and methods. Materials from medical histories of patients hospitalized at the National Center of Ophthalmology named after Academician Z. Aliyeva (12 882 cases) for 2019 (from January 1 to December 31) were used. The need of hospitalized patients for hightech ophthalmological care was determined in accordance with the list of types of hightech medical care. The volume of demand of the population of Azerbaijan for GPs by type of indications and interventions was established per 100 thousand population with the determination of the average error of the indicator.Results. 14.5 ± 0.3 % of ophthalmological patients received hightech ophthalmological care. The main types of hightech ophthalmological care necessary to meet the needs of the population are transpupillary, microinvasive energetic opticalreconstructive and endovitreal 23.25 gage surgery for vitreoretinal pathologies of various origins (75.3 % of all types of operations; 16.63 ± 0.44 operations per 100 thousand population). The second place in the structure is occupied by complex surgical treatment of glaucoma, including microinvasive energy opticalreconstructive and laser surgery with possible implantation of silicone valve or metal drainage (11.3 % of all operations; 2.48 ± 0.17 operations per 100 thousand population).Conclusions. In Azerbaijan, the leading reasons for providing hightech ophthalmological care are: cataracts complicated by lens luxation, glaucoma, pathology of the vitreous body, retina and choroid (27.0 % of all reasons; 5.96 ± 0.26 cases per 100 thousand population); retinal detachment and tears, tractional retinal detachment, other forms of retinal detachment in adults and children, complicated by pathology of the cornea, lens, vitreous body (22.1 % of all cases, 4.89 ± 0.24 cases per 100 thousand population). The most common type of hightech ophthalmological care is transpupillary, microinvasive energetic opticalreconstructive and endovitreal surgery for vitreoretinal pathologies of various origins (75.3 % of all types; 16.63 ± 0.44 cases per 100 thousand population).